Identificación de vulnerabilidades, gestión de riesgos de inundaciones y adaptación al cambio climático en el cono norte de Arequipa: avances y perspectivas (2014 -2016) - Hernando Núñez del Prado Simons (2017)
Disaster Risk Management and Adaptation to Climate Change are processes of high priority within the planning of the Cono Norte zone of Arequipa which is a vulnerable growing population. The proposed method comprise an assessment of the components contributing to vulnerability face of the Climate Change, being an important part in adaptation planning. We have identified 6 types of vulnerability: Economic, Physical, Technical, Social, Cultural, and Institutional that the Cono Norte population shows face to the recurrent flood risk every year. We propose to manage the risk by means of reducing vulnerabilities on the base of estimating the flood risk, organizing the population, and forcing authorities to implement policies and strategies to face multiple hazards known (floods, earthquakes, and others)